THE MONITORING OF SPREADING AFRICAN SWINE FEVER IN UKRAINE AND POLTAVA REGION - Omelchenko, G. O.; Petrenko, M. O.; Avramenko, N. O. (Scientific Progress & Innovations, 2019)
In recent years, African swine fever (ASF) has put the Ukrainian pig breeding sector at risk. The spreading of ASF in Ukraine has already led to serious social-economic consequences. Although certain results have been achieved in fighting this disease, its negative impact on the domestic meat market is continuing. In 2014, 16 cases were detected in the north-eastern part of the country, on the territory of three regions (Luhansk region, Chernihiv region, and Sumy region). In total, in 2015, 40 cases were registered, and in 2016 their number increased by almost 2.3 times and reached the maximum (91 cases). In 2016, the disease was spreading even more quickly, and during the year, 91 outbreaks of ASF (84 among domestic and 7 among wild pigs) in 16 regions of Ukraine were confirmed. In 2017, 163 cases (119 among domestic, 38 among wild and 6 infected animals) were confirmed in 23 regions of Ukraine. From January 1 to February 22, 2018, 37 cases of this disease were officially registered, in particular in January 2018 − 18 outbreaks. In 2015, there were five unfavorable places in connection with African swine fever in Poltava region – Pyriatyn, Hrebinka, Kremenchuk, and Hlobyne districts. In all cases, the cause of carrying the pathogen is irresponsible attitude of citizens to the requirements of the current veterinary legislation. In 2016, 10 unfavorable cases concerning African swine fever (Khorol, Velyka Bahachka, Hlobyne, Lubny, Lokhvytsia, Hadiach, Kobeliaky, Hrebinka districts and the town of Hadiach) were registered in Poltava region including 4 cases among wild boars and 6 among domestic pigs. In 2017, 21 unfavorable places in connection with African swine fever in Poltava region were registered including domestic pigs: 16 individual farms, 3 farms of different forms of ownership and 2 places in wild fauna, in which 193 domestic pigs fell ill and died and 2 corpses of wild boars were found (Velyka Bahachka, Shyshaky, Kotelva, Karlivka, Chutove, Lubny, Hlobyne, Pyriatyn, Hadiach, Kobeliaky, Semenivka, Orzhytsia districts and the town of Lubny). In 2018, 8 unfavorable places concerning African swine fever (Chutove, Kremenchuk, Poltava, Dykanka, Myrhorod, Kotelva, Lubny, and Kobeliaky districts) were registered in Poltava region. The real level of ASF incidence in Ukraine remains uncertain due to the limited ability of the state veterinary services to quickly detect and confirm the diagnosis of the disease. According to experts’ forecasts, if there is no timely and effective control of the disease, the negative impact of its spreading is likely to increase and create new risks for farmers and pork processing enterprises.